2020
DOI: 10.4314/ahs.v20i2.37
|View full text |Cite
|
Sign up to set email alerts
|

Elabela levels in patients with type 2 diabetes: can it be a marker for diabetic nephropathy?

Abstract: Backround: Elabela (ELA) is a hormone that is secreted at high levels in the kidneys of a healthy adult. This study aims to investigate whether serum ELA levels of patients with Type 2 Diabetes vary with the severity of renal damage. Methods: Our study included 50 healthy control subjects and 100 diabetic patients, who were categorized into groups based on urine albumin/creatinine ratios (ACR). Patients included in the study were assigned to four groups: Group 1 (healthy control), Group 2 (ACR<29mg/g)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Particularly, the serum Elabela level decreased progressively with the progression of DN; moreover, the serum Elabela level has a negative correlation with blood pressure, retinopathy, serum creatinine, and urinary albumin/creatinine ratio and has a positive correlation with the estimated glomerular filtration rate (29). A similar result was also confirmed by Erhan et al They found that the Elabela level was higher in healthy individuals when compared with diabetic patients without microalbuminuria and even higher in diabetic patients without microalbuminuria when compared to patients with advanced albuminuria (35). These results suggest that Elabela may be an important clinical prognostic marker.…”
Section: Diabetic Nephropathysupporting
confidence: 76%
See 1 more Smart Citation
“…Particularly, the serum Elabela level decreased progressively with the progression of DN; moreover, the serum Elabela level has a negative correlation with blood pressure, retinopathy, serum creatinine, and urinary albumin/creatinine ratio and has a positive correlation with the estimated glomerular filtration rate (29). A similar result was also confirmed by Erhan et al They found that the Elabela level was higher in healthy individuals when compared with diabetic patients without microalbuminuria and even higher in diabetic patients without microalbuminuria when compared to patients with advanced albuminuria (35). These results suggest that Elabela may be an important clinical prognostic marker.…”
Section: Diabetic Nephropathysupporting
confidence: 76%
“…It is reported that Elabela can ameliorate apoptosis via regulating the mitochondrial function ( 33 ). Recently, Elabela has been demonstrated to decrease kidney injury ( 34 ), and serum Elabela level in type 2 diabetes patients is closely related to the severity of renal injury ( 35 ). In addition, Elabela has been reported to improve endothelial cell function via the PI3K/Akt signaling pathway ( 36 ).…”
Section: Apelin–apj Receptor System Discovery and Developmentmentioning
confidence: 99%
“…In patients with stable angina pectoris and atrial fibrillation in stable disease, ELA levels will be reduced ( Cui et al, 2021 ; Diakowska et al, 2021 ). Further, compared with healthy people, serum ELA is lower in patients with diabetic nephropathy ( Onalan et al, 2020 ). In patients with CKD, the serum ELA level gradually decreases with the reduced GFR level, with the lowest values observed in patients with CKD5 ( Lu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“… 74 An additional study conducted in 50 healthy and 100 diabetic patients found a similar negative correlation between serum ELABELA and urinary albumin creatinine ratio. 75 …”
Section: Diabetic Complicationsmentioning
confidence: 99%